'O antigenic' polysaccharide specific memory B cell responses in Bangladeshi Cholera patients infected with Vibrio cholerae O1 - Sami, Md. Israk Nur (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2015.